Development and Application of a Stepwise Assessment Process for Rational Redesign of Sequential Skills-Based Courses - Gallimore, Casey E. (Am J Pharm Educ, 2016)
Objective. To develop and apply a stepwise process to assess achievement of course learning objectives related to advanced pharmacy practice experiences (APPEs) preparedness and inform redesign of sequential skills-based courses. Design. Four steps comprised the assessment and redesign process: (1) identify skills critical for APPE preparedness; (2) utilize focus groups and course evaluations to determine student competence in skill performance; (3) apply course mapping to identify course deficits contributing to suboptimal skill performance; and (4) initiate course redesign to target exposed deficits. Assessment. Focus group participants perceived students were least prepared for skills within the Accreditation Council for Pharmacy Education’s pre-APPE core domains of Identification and Assessment of Drug-related Problems and General Communication Abilities. Course mapping identified gaps in instruction, performance, and assessment of skills within aforementioned domains. Conclusions. A stepwise process that identified strengths and weaknesses of a course, was used to facilitate structured course redesign. Strengths of the process included input and corroboration from both preceptors and students. Limitations included feedback from a small number of pharmacy preceptors and increased workload on course coordinators.